Population structure and genetic variability in the Murrah dairy breed of water buffalo in Brazil accessed via pedigree analysis - Mendes Malhado, Carlos Henrique; Mendes Malhado, Ana Claudia; Souza Carneiro, Paulo Luiz; Ramos, Alcides de Amorim [UNESP]; Ambrosini, Diego Pagung; Pala, Akin (Springer, 2012)
The objective of this study was to use pedigree analysis to evaluate the population structure and genetic variability in the Murrah dairy breed of water buffalo (Bubalus bubalis) in Brazil. Pedigree analysis was performed on 5,061 animals born between 1972 and 2002. The effective number of founders (fe) was 60, representing 6.32 % of the potential number of founders. The effective number of ancestors (fa) was 36 and the genetic contribution of the 17 most influent ancestors explained 50 % of the genetic variability in the population. The ratio fe/fa (effective number of founders/effective number of ancestors), which expresses the effect of population bottlenecks, was 1.66. Completeness level for the whole pedigree was 76.8, 49.2, 27.7, and 12.8 % for, respectively, the first, second, third, and fourth known parental generations. The average inbreeding values for the whole analyzed pedigree and for inbreed animals were, respectively, 1.28 and 7.64 %. The average relatedness coefficient between individuals of the population was estimated to be 2.05 %-the highest individual coefficient was 10.31 %. The actual inbreeding and average relatedness coefficient are probably higher than estimated due to low levels of pedigree completeness. Moreover, the inbreeding coefficient increased with the addition of each generation to the pedigree, indicating that incomplete pedigrees tend to underestimate the level of inbreeding. Introduction of new sires with the lowest possible average relatedness coefficient and the use of appropriate mating strategies are recommended to keep inbreeding at acceptable levels and increase the genetic variability in this economically important species, which has relatively low numbers compared to other commercial cattle breeds. The inclusion of additional parameters, such as effective number of founders, effective number of ancestors, and fe/fa ratio, provides better resolution as compared to the inclusion of inbreeding coefficient and may help breeders and farmers adopt better precautionary measures against inbreeding depression and other deleterious genetic effects.
Keywords: Average relatedness coefficient; Completeness pedigree; Inbreeding coefficient